2002
DOI: 10.1093/jn/132.7.1921
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation Alters Protein Metabolism in Several Organs of Adult Rats

Abstract: Despite the prevalence of chronic inflammatory diseases in developed countries, few studies have considered the metabolic alterations observed in these disorders. To determine which perturbations in protein metabolism occur during chronic inflammation, and the consequences they have on nutritional requirements, a model of ulcerative colitis was adapted for use in adult rats. Adult Sprague-Dawley male rats (9 mo old) received dextran sulfate sodium (DSS) in their drinking water at 50 g/L for 9 d, then at 20 g/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 46 publications
6
52
0
Order By: Relevance
“…has been shown that an acutely induced systemic inflammation results in increased protein catabolism and altered protein synthesis (24,33), showing the importance of inflammation in protein metabolism. Furthermore, chronic inflammation induced by DSS treatment in rats resulted in a stimulation of protein synthesis in various splanchnic organs, i.e., the spleen and intestine, whereas muscle protein turnover was reduced (24).…”
Section: Discussionmentioning
confidence: 99%
“…has been shown that an acutely induced systemic inflammation results in increased protein catabolism and altered protein synthesis (24,33), showing the importance of inflammation in protein metabolism. Furthermore, chronic inflammation induced by DSS treatment in rats resulted in a stimulation of protein synthesis in various splanchnic organs, i.e., the spleen and intestine, whereas muscle protein turnover was reduced (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, GSH is not taken up directly by most cell phenotypes and must first be broken down into its component amino acids (cysteine, glutamate, and glycine) by enzymes including δ-glutamyltranspeptidase. 7 Administration of N-acetyl-cysteine in the trinitrobenzene sulfonic acid rat model attenuated this chemically induced colitis, 8 which suggests that GSH precursors may be beneficial in the acute relapse of IBD. Dextran sodium sulfate (DSS) treatment of mice mimics IBD in that it provokes inflammation and macrophage activation, with subsequent loss of epithelial integrity, and increases luminal Gram-negative flora.…”
mentioning
confidence: 99%
“…It is well known that in liver and skeletal muscles, tumor-induced negative nitrogen balance can promote intracellular production and extracellular release of glutamine (Medina et al, 1992). I n a d d i t i o n , i t w a s r e p o r t e d t h a t i n a c h ronic inflammatory process, the amino-acid metabolism could be influenced even in many remote organs: For instance, absorption of blood cysteine and methionine were both elevated immediately after glutathione synthesis was increased in the liver (Mercier et al, 2002).…”
Section: Metabolic Changes In Various Remote Normal Organsmentioning
confidence: 99%